2009
DOI: 10.1002/chem.200901838
|View full text |Cite
|
Sign up to set email alerts
|

Metastable Aluminum(I) Compounds: Experimental and Quantum Chemical Investigations on Aluminum(I) Phosphanides—An Alternative Channel to the Disproportionation Reaction?

Abstract: The well known thermodynamic instability of Al and Ga monohalides is caused by the favored disproportionation process to the bulk metal and the trihalides. During this highly complex process, a number of metalloid clusters that are intermediates on the way to the metal have been trapped. Therefore, all observations in the field of metalloid Al/Ga clusters have been traced to this favored disproportionation process. The failure to form phosphanide-substituted Al clusters, in contrast to the generation of simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 76 publications
(58 reference statements)
3
15
0
Order By: Relevance
“…[9][10][11] The latter complex contains a naked P 3-ion that presumably results from a successive ligand-based decomposition process leading to the Al 3 P moiety. DFT studies showed how the ligand redox vs. disproportionation pathways followed different routes from the Al I precursors to give markedly different products.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] The latter complex contains a naked P 3-ion that presumably results from a successive ligand-based decomposition process leading to the Al 3 P moiety. DFT studies showed how the ligand redox vs. disproportionation pathways followed different routes from the Al I precursors to give markedly different products.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25] Here we consider the use of graphene as a template for growing small metalloid aluminum clusters. The pioneering work of Schnöckel and co-workers has led to the development of many striking group 13 metalloid systems, [29][30][31][32][33][34][35] including the large Al 77 [N(SiMe 3 )] 2 20 , Al 50 Cp 1 2 ⇤ , and Si@Al 56 [N(2, 6-iPr 2 C 6 H 3 )SiMe 3 ] 12 . Metalloid clusters are often conceptualized as metastable intermediates on the way to formation of a bulk metal, and have been a) Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…All these systems are synthesized from AlX (X=Cl, Br, or I) monovalent aluminum halide precursors formed in a specialized cocondensation apparatus. [14,15,16,17,18] 12 . These clusters crystallize into low-symmetry molecular crystals that are very airsensitive; in this report we focus on isolated clusters for comparison with recent gas-phase cluster studies in ultra-high vacuum.…”
Section: Introductionmentioning
confidence: 99%